Karstifikasi dan Pola Struktur Kuarter Berdasarkan Pemetaan Lapangan dan Citra SRTM Pada Formasi Wapulaka, Pasar Wajo, Buton, Sulawesi Tenggara. - Yuniarti Yuskar; Harisma Buburanda; Tiggi Choanji (Universitas Islam Riau (UIR) Press, 2017)
Karstification process occurs as a result of dissolution on limestone lithology formed in typical morphology of caves, rounded or elongated pits and conical hills. This also related with structural pattern that also intesively occurs at western part of Buton Island. Research area located at lattitude 5027’0” S – 5032’0’’ S and longitude 122049’30” E - 122052’30” E. Purpose of this research was to identified karst landscape and karstificatiom process on Wapulaka Formation and recognize the structural pattern on this formation. By using field observation and SRTM data interpretation we considered that karst formations formed on Wapulaka Formation was Quarter limestone which diagenesis process of dissolution forming karst landform also related with uplifted event at pliocene – pleistocene. This formed related with complex interaction between the geology, climate, hydrology and biological factors that created various landscape morphology such as caves, underground river, stalagtite, stalagmite and others cave ornament.